Molecular events underlying interleukin‐6 independence in a subclone of the CMA‐03 multiple myeloma cell line. Issue 2 (5th November 2013) - Verdelli, Donata; Nobili, Lucia; Todoerti, Katia; Mosca, Laura; Fabris, Sonia; D'Anca, Marianna; Pellegrino, Elisa; Piva, Roberto; Inghirami, Giorgio; Capelli, Chiara; Introna, Martino; Baldini, Luca; et al.
<x xml:space="preserve">Abstract</x> We explored the molecular mechanisms involved in the establishement of CMA‐03/06, an IL‐6‐independent variant of the multiple myeloma cell line CMA‐03 previously generated in our Institution. CMA‐03/06 cells grow in the absence of IL‐6 with a doubling time comparable with that of CMA‐03 cells; neither the addition of IL6 (IL‐6) to the culture medium nor co‐culture with multipotent mesenchymal stromal cells increases the proliferation rate, although they maintain the responsiveness to IL‐6 stimulation as demonstrated by STAT1, STAT3, and STAT5 induction. IL‐6 independence of CMA‐03/06 cells is not apparently due to the development of an autocrine IL‐6 loop, nor to the observed moderate constitutive activation of STAT5 and STAT3, since STAT3 silencing does not affect cell viability or proliferation. When compared to the parental cell line, CMA‐03/06 cells showed an activated pattern of the NF‐κB pathway. This finding is supported by gene expression profiling (GEP) analysis identifying an appreciable fraction of modulated genes (28/308) in the CMA‐03/06 subclone reported to be involved in this pathway. Furthermore, although more resistant to apoptotic stimuli compared to the parental cell line, CMA‐03/06 cells display a higher sensibility to NF‐κB inhibition induced by bortezomib. Finally, GEP analysis suggests an involvement of a number of cytokines, which might contribute to IL‐6 independence of CMA‐03/06 by stimulating growth and antiapoptotic processes. In conclusion, the parental cell‐line CMA‐03 and its variant CMA‐03/06 represent a suitable model to further investigate molecular mechanisms involved in the IL‐6‐independent growth of myeloma cells. © 2013 Wiley Periodicals, Inc.